KEKUATAN NILAI EMOSIONAL DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PERUSAHAAN JASA EKSPEDISI - Nisrina, Mella Azhar; Ramdan, Asep M.; Mulia Z, Faizal (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.06.TAHUN 2019DO - 10.24843/EEB.2019.v08.i06.p01, 2019)
The purpose of this study is measure the influence of emotional value and quality of service on customer satisfaction in expedition service companies. The method used in this study is the use the type of sampling includes in the random sampling sample by distributing 206 questionnaires to consumers. The analysis technique using multiple linear regression analysis techniques, including test coefficient of determination, multiple correlation coefficient, simultaneous test (F test), and partial test (t test). The results of the test coefficient of determination seen from the value (adjusted R 2 ) of 0.854 can be interpreted that the effect of Emotional Value and Service Quality on consumer satisfaction is 85.7%. The remaining 14.6% is influenced by other factors not explained in this study. Based on the multiple correlation coefficient test seen from the R value of 0.925, it shows that there is a very strong relationship between emotional value and service quality with customer satisfaction. Based on the F test the probability value sig. 0.00 <0.05, which means that together Emotional Value (X1) and Service Quality (X2) have a significant effect on customer satisfaction (Y). Based on the t test shows that Emotional Value (X1) does not have a significant effect on customer satisfaction (Y), Service Quality (X2) has a significant effect on customer satisfaction (Y).